Building a model of the flow in a nozzle-flapper valve of the HP-3 control pump to improve the stability of characteristics - Lytviak, Oleksandr; Trishch, Roman; Khomiak, Eduard; Kochuk, Serhii; Khomenko, Svitlana; Tiupa, Ihor (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the flow of a viscous incompressible fluid in a nozzle-flapper valve used as part of the free turbine speed controller in the HP-3 pump-regulator of the TV3-117 turboprop helicopter engine. The task addressed relates to a need for detailed calculations of the fluid flow because of unsatisfactory operation of the valve under actual operating conditions. An additional difficulty was the contradictory data on the characteristics of such valves in the literature, which made it impossible to determine the flow characteristics and directions for improving the design. This paper reports the results of numerical calculations of the flow in the valve performed in the SolidWorks Flow Simulation environment. A mathematical model is proposed that takes into account the influence of the design mesh on the accuracy and computational time volume, as well as ways to improve accuracy without a significant increase in resources. The model was verified by comparing it with the manufacturer’s experimental data. The results have made it possible to solve the problem through the detailed construction of the model taking into account the valve geometry and optimization of the computational mesh, which ensured a balance between accuracy and computational speed. The results are attributed to the application of state-of-the-art hydrodynamic calculation software, precise mesh tuning, as well as proper validation of the model to reflect the actual physical processes in the valve. The model built makes it possible to study the flow in the valve and could be used to analyze the impact of manufacturing defects. The model is suitable for parametric studies and modification of valves in helicopter engines of the TV3-117 type or similar systems. The model could also be adapted for other systems requiring flow analysis in similar valves